Exploring an action research process of multimodal learning system design for online learners of English language education in a Chinese university - Cao, Wen (2010)
This thesis is my professional autobiography that records an action research process of three full cycles ranging from 2004 to 2006. I follow a narrative style and a first person perspective to present this process in loyalty to the action research nature and my research reality. I work at an online institute (the Institute) of a Chinese university and I am responsible for course design and development of degree-bearing courses in English language education via online delivery to learners nationwide. My job is contextualized in a situation in China where online course design and development booms in practice, yet it lacks theoretical guidelines, quality research with responsive approaches and staff with professional identity and practice. I started my research in 2004 with a mono-commitment -- a real-situation task of adapting the courseware of an "orientation” module of a post-diploma BA course in English language education. I worked alone as both a researcher and a practitioner, only to find that the task involved more than just courseware design - it dealt with subject matter in that online course design and development was a process as well as a product that aimed at the construction of a learning system (the "What" issue); it also dealt with a methodological issue of selecting a research approach that could accommodate my research need and situation (the "How" issue). I started my second research cycle in 2005 with dual commitments – the exploration of instructional design as a subject matter guideline and action research as a responsive research methodology. I led a team of 3 tutor-researchers and 15 learner-researchers through a process of "plan -- act -- analyze and reflect” during the design, development, implementation and evaluation phases of the "orientation" module. Two issues emerged from this research cycle. One was that there existed four major tensions between instructional design and the learners' reality: time design, media selection, support design in relation to interaction and group learning, and assessment design. The other was that action research could be applied as an effective approach to professional development. I conducted my third research cycle in 2006 with tri-commitments – professional development (the "Who" issue) of 12 new staff at the Institute in addition to a further exploration of instructional design (the "What" issue) and action research (the "How" issue). This research cycle revealed that the interventional strategies worked to some extent, but some issues persisted and new issues emerged. Among them, the tensions between instructional design and the learners' reality, and the multi-faceted context of the research were repeatedly recognized. The three research cycles have informed my further research to establish a paradigmatic and practical framework that can integrate the "What", the "How" and the "Who" issues. This framework is termed multimodal learning system design that adopts a design, learning, multimodal and ecological view to guide a cyclical process that involves a community of practice in inquiry and reflection as well as all the major stakeholders (e.g. designers, tutors, administrators and learners) and a product that creates a learning system. This framework is valued for its responsiveness to sustainable improvements and changes in the online education field full of innovation and challenges in theory, research and professionalism.